2021
DOI: 10.3390/su13168748
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development and Renewables in Southeast Asian Countries—The Role of Organic Waste Materials

Abstract: This paper aims to fill the existing gap by investigating the linkage between organic waste materials, financial development and renewables in Southeast Asia; this is the very first study covering this area. Using panel data of ten economies in this area in the period of 1990–2016 and estimating the advanced regression method in statistics of pooled mean group (PMG) estimates, the paper aims to examine the panel unit root tests in the first and second generations, as well as cointegration tests followed by Ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
(49 reference statements)
1
13
0
Order By: Relevance
“…However, the impact turns negative in the later periods due to the negative externalities of FDI projects on the environment, low technology and sustainable development. In addition, Nguyen and Nguyen (2021) [21] also confirmed a positive relationship between FDI and economic growth, including in the agricultural sector.…”
Section: Foreign Direct Investment and Economic Growthmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the impact turns negative in the later periods due to the negative externalities of FDI projects on the environment, low technology and sustainable development. In addition, Nguyen and Nguyen (2021) [21] also confirmed a positive relationship between FDI and economic growth, including in the agricultural sector.…”
Section: Foreign Direct Investment and Economic Growthmentioning
confidence: 95%
“…Environmental protection is the practice of protecting and maintaining the natural environment, and environmental degradation needs to be repaired [5]. In the light of attracting foreign investment, environmental quality has been greatly damaged all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of sugarcane bagasse ranked top in the world at 18575.1 million tons, followed with rice straw, corn straw, wheat straw and barley straw respectively, and the last are cotton and fiber crops. Asia is the region that produces the most food with East Asian countries like China and India major growers of crops [58]. It is estimated that 1000 million tons of crop straw are produced yearly in China [59], while India produces a total of 500 million tons [60].…”
Section: Crop Strawmentioning
confidence: 99%
“…Nguyen also demonstrated that regional characteristics have an impact on Vietnam's capacity to attract FDI. He just focused on the attraction of FDI inflows in each province in Vietnam [19][20][21].…”
Section: Literature Reviewmentioning
confidence: 99%